Analysis of the Cost and Profit on Beef Cattle Production between Grazing System and Intensive System of Farmers in Narathiwat Province - Thaiburi, Narid; Trimanee, Sunee; Thepkun, Prajak; Limcharoen, Somnuek; Jun-iad, Jamnong (Princess of Naradhiwas University Journal, 2019)
The aims of this research were to study beef cattle production between grazing system and intensive system and to analyze beef cattle production cost and returns in both system of beef cattle farming. The data were collected by interviewing 160 medium sized cattle farm sample. A sample of 160 cases were selected using purposive sampling technique. The data of total cost and the selling price were evaluated the net returns. The results showed that the farmers in Narathiwat province had been raising cattle with grazing system and intensive system at 77.50% and 22.50%, respectively. Furthermore, the production cost of grazing system was 14,647.06 baht per head and selling price was 22,500.00 baht per head. This led to the net return of 7,852.94 baht per head within 1.5 years. On the other hand, the intensive system had the production cost 29,203.19 baht per head and the selling price was 32,210.20 baht per head. The net return of this system was 3,007.01 baht per head within 5 months. From the finding, the recommendation of upstream production development of cattle was to separate cows and raised with intensive system from fattening cattle in barns before selling the cattle to the market.